Peran pancasila dalam menghadapi tantangan globalisasi: Pengaruh budaya luar terhadap masyarakat Indonesia - Khutmala, Rohadatul Firda (Maliki Interdisciplinary Journal, 2025)
The era of globalization has brought a strong influence of foreign cultures into Indonesian society. These influences appear through technology, social media, lifestyle, and increasingly intense intercultural interactions. This situation poses challenges to the existence of Pancasila values as the nation's ideology and worldview. This study aims to analyze the role of Pancasila in facing the influence of foreign cultures on Indonesian society amid globalization. The research method used is a literature review by examining previous studies from the UIN Maulana Malik Ibrahim Malang repository and other relevant literature. The results show that Pancasila has a strategic function as a value filter that can absorb positive aspects of foreign cultures without losing national identity. However, its effectiveness depends on consistent implementation in education, family, and social environments. Strengthening Pancasila values in daily life is the key for Indonesia to adapt to globalization while preserving its cultural identity.